COMPARISON OF CAPTURE RESULTS OF CAPTURE TRACKS OF BOATS AT THE PREVIOUS AND AFTER MIDDLE NIGHT AT KOTO XI DISTRICT TARUSAN, PESISIR SELATAN DISTRICT, WEST SUMATERA PROVINCE - Ilham Caniago; Syaifuddin Syaifuddin; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACK This research was conducted from June to July in Koto XI Tarusan subdistrict, Pesisir Selatan Regency, West Sumatra Province. This study aims to determine the comparison of boat chart catches in the amount of weight (kg), number of individuals (tails) and fish species before and after midnight fishing in Koto XI Tarusan District, Pesisir Selatan Regency, West Sumatra Province. The method used in this study is a participatory method, which is catching data on catches in the fishing ground (fishing ground) by participating in the process of catching boat fishing gear. All data obtained are processed and processed by t test analysis. The results of this study based on statistical tests conducted there are differences in catches of boat chart fishing equipment based on the amount of weight before midnight and after midnight where thit 4.10 is greater than ttab 3.067 so the initial hypothesis is rejected means that there is a difference in the number of results composition catch between the time before midnight and after midnight. Keywords: Boat Chart Fishing Equipment, Comparison, Test Analysis t